Epidemiology and risk factors for candidaemia at Chris Hani Baragwanath hospital (2009-2010) - Seetharam, Sharona (My University, 2017)
Background Invasive Candida infections (ICI) have emerged as an important cause of increased morbidity and mortality in specific patient populations in recent years. Multiple risk factors coupled with changes in epidemiology have made clinical management of these patients challenging. A laboratory-based surveillance project, Tracking Resistance to Antifungal drugs for Candida species in South Africa (TRAC-SA) was conducted at Chris Hani Baragwanath Hospital (CHBH) from 2009 to 2010 and allowed for collection of laboratory information related to episodes of candidaemia, delineation of the situation at the hospital and distribution of information to relevant stakeholders to help make informed clinical decisions. Objective Determine the clinical epidemiology and risk factors for bloodstream Candida infection at CHBH over an 18-month period Methods A retrospective, cross-sectional analysis was carried out on cases of blood culture-confirmed candidaemia from inpatients from 1 February 2009 until 31 August 2010. These cases were identified from the TRAC-SA database, inpatient files were traced and clinical data recorded on a standard case report form. Additional laboratory data of selected tests done within 72 hours of the initial blood culture were obtained from the National Laboratory Health Service Corporate Data Warehouse (CDW). Results A total of 167 episodes of candidaemia were identified during the study period with an incidence of 2.09 per 1000 admissions. The distribution of episodes occurred among 55 children (33%), 41 adults (25%) and 71 neonates (43%). The overall species distribution was Candida species other than C. albicans (98/167, 58.7%) and C. albicans (69/167, 41.3%). Candida species other than C. albicans comprised mainly of C. parapsilosis (73/167, 43.7%), C. glabrata (10.2 %, 17/167) and other species combined including C. tropicalis and C. krusei (8/167, 4.7%). Factors associated with C. albicans (versus Candida species other than C. albicans) infection included older age, use of 2 or more antibiotics, use of broad spectrum antibiotics specifically meropenem, aminoglycosides, vancomycin, co-trimoxazole and mechanical ventilation (p < 0.001). The overall case-fatality was 59/163 (35.3%). The highest case fatality was noted among adults with C. albicans infection, i.e. 15/22 (68.18%). Significant risk factors associated with in-hospital mortality were use of central lines, urinary catheters, total parenteral nutrition, 2 or more antibiotics, beta lactam - beta lactamase inhibitors, proton pump inhibitors, aminoglycoside and abdominal surgery (p < 0.01). Of the C. parapsilosis isolates tested, 40 (57. 9%) tested non-susceptible to fluconazole. Risk factors associated with fluconazole resistance included neonatal age, involvement of the respiratory system, mechanical ventilation, chemotherapy, use of a prior antifungal agent and use of 2 or broader spectrum antibiotics (p<0.01). Of 71 neonates, 16 (22.5%) received empiric antifungals, in comparison to children (5/55, 9.0%) and adults (4/41, 9.7%) (p = 0.272). Conclusion CHBH had a high incidence of candidaemia with a predominance of Candida species other than C. albicans especially in the neonate age group. Risk stratification of in-patients is of paramount importance in choice of empiric antifungal drug due to the differing azole resistance patterns observed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment for the requirements for the degree of Master of Medicine in Microbiology. Johannesburg, 2017
Keywords: Candidemia Epidemiology